The establishment of a porcine rheumatoid arthritis model: Collagen induced arthritis minipig model - Won Jae Lee; Ji Yeon Kim; Tammy Peijung Wu; Lisa Soyeon Park (Elsevier, 2016)
Rheumatoid arthritis (RA) research has been largely dependent on collagen induced arthritis (CIA) rodent models, however, they may not translate well to humans due to innate differences in the size, physiology and lifespan. The present study aimed to establish a CIA porcine model with the physical, hematological, histopathological and etiological properties closer to their human equivalent in an attempt to better meet the needs of RA research. Three month old minipigs were administered of bovine type II collagen (CII) emulsified with complete Freund's adjuvants on Day 1 and incomplete Freund's adjuvants on Day 22, via an intradermal or intra-articular route. The clinical, radiological and hematological assessments of immunized animals were made periodically until Day 43, during which period the onset and progression of arthritis was recorded and characterized. In addition, the histopathological and micro-tomographic assessments of the cartilage degradation with regard to mononuclear cell infiltration, and joint deformity indicated a higher severity in the intradermal injection group over the intra-articular group. With confirmation of the susceptibility to heterogeneous CII for arthritis induction in minipig, the potential suitability of this test system as a large animal model for RA has been demonstrated.